Creating Sustainable Competitive Advantage for a Mid-Sized Business Institute: A Case Study for Market-based Management (MBM) Approach - Uzma Zaidi (Language, Literature and Education: Research Updates Vol. 1, 2025)
The higher education sector in the UAE has witnessed escalating competition, resulting in an increase in the number of national and international universities operating here. This study aims to propose and test a conceptual model, Market-based Management (MBM) which is a management philosophy designed to enable organizations to succeed through internal cultural shifts. In order to get some insightful understanding, this research examines a mid-sized business institute, SZABIST-Dubai by using a qualitative research methodology of case study. The research adopted the five attributes of Market-Based Management (MBM) to SZABIST and some significant findings were the survival and profitability challenges faced by SZABIST and a unidirectional centralized decision-making model that is adapted currently at the institute. The outcome of this paper is its proposition of Market-Based Management (MBM) as a tool to evolve into a knowledge-based learning organization that is more responsive to regional and local challenges. The most significant contribution of this paper towards this objective is the founding of Task Teams that transform tacit learning into explicit knowledge through the process of socialization. This paper can be useful for future researchers who wish to extend these findings to other higher educational institutes.